Facile H2PdCl4-induced photoreforming of insoluble PET waste for C1-C3 compound production - Li, Dani Tong; Yu, He; Huang, Ying (Frontiers in Chemistry, 2023)
To date, over 8 billion tons of plastic have been produced and used in daily life. The traditional method including landfill, incineration and biodegradation can no longer meet the environmental and economic requirements, and concerns regarding the plastic pollution is becoming increasingly serious that new techniques to appropriately manage these polymer wastes are desperately needed. Previous works have demonstrated a valuable approach to convert the water-soluble oligomer fragments with small molecular size in plastic to useful chemical via photoreforming (PR). But the challenge of the insoluble oligomer fragments of complex chemical structures and larger molecular size from plastic waste remains unexplored. In this work, we report a facile H2PdCl4-induced activation on PET substrate, for PR of PET bottles to produce C1-C3 compounds, without using any sacrificial reagent or photocatalysts. This work will be helpful for solving the most challenging tasks of the plastic PR.